Prospects for Physical Therapy in Rheumatoid Arthritis: Literature Review - Dana Taizhanova; Olga Pokrashenko; Anna Shalygina (Healthcare, 2026)
Background: The incidence of rheumatoid arthritis is steadily increasing worldwide, resulting in a growing number of individuals who may lose the ability to perform self-care activities and professional duties, thereby reducing their quality of life. Rheumatoid arthritis represents a significant social problem, limiting the ability of the working population to lead a full life. A comprehensive approach to the treatment of patients with rheumatoid arthritis, including both pharmacological therapy and an individualized rehabilitation program, is of strategic importance for maintaining their functional status. Materials and Methods: A review of modern physiotherapy methods (physical factors) in patients with rheumatoid arthritis was conducted in the international scientific databases Web of Science, PubMed, Google Scholar, and Elibrary over a seven-year period to identify an alternative approach to the treatment of this disease. Results: The search identified 12 articles presenting the results of clinical studies (3), cross-sectional study (1) and randomized clinical trials (8). These studies investigated physiotherapy interventions in patients with RA and highlighted the potential value of exploring alternative treatment approaches for this patient population. Despite substantial heterogeneity in the interventions, treatment protocols, and combinations of physical factors used, all of the reviewed methods demonstrated positive effects. Conclusions: Physiotherapy interventions may have a positive impact on the clinical course of rheumatoid arthritis; however, the available evidence is insufficient to draw definitive conclusions regarding their effectiveness, primarily due to the lack of long-term follow-up data and substantial heterogeneity in the number and design of treatment sessions, as well as in the physical factors applied. The long-term effects of physiotherapy interventions remain insufficiently studied and warrant further research aimed at developing standardized and evidence-based treatment protocols.